KECERNAAN SERAT KASAR DAN BETN (BAHAN EKSTRAK TANPA NITROGEN) RANSUM KOMPLIT BERBASIS TEBON JAGUNG PADA SAPI PERANAKAN ONGOLE - Aling, Christanto; Tuturoong, R.A.V.; Tulung, Y.L.R.; Waani, Merci R. (Universitas Sam Ratulangi, 2020)
DIGESTIBILITY OF CRUDE FIBER AND NNFE (NON NITROGEN FREE EXTRACT) COMPLETE FEED BASED ON CORN FORAGE ON ONGOLE CROSSBREED CATTLE. This Research was conducted to evaluate digestibility of crude fiber and NNFE (non nitrogen free extract) complete feed based on corn forage and king grass on ongole crossbreed cattle. The total of 14 ongole crossbreed cattle at age of 1,5 – 2 years old with the body weight of 180 – 250 kilogram were used in this study. The completely using the analysis t-Test (Two-Sample Assuming Unequal Variences) randomized design involving 2 treatments and 7 replications in each treatment was applied at the experimental unit. The treatments of this research were consisted of Ra = corn forage 50% + concentrate 50% and Rb = corn forage 25% + king grass 25% + concentrate 50%. The results of this research showed that consumption of crude fiber was not significantly (P>0,05) but digestibility of crude fiber was very significantly (P<0.01). Digestibility of NNFE was significantly (P<0.05). Based on the result of this study can be concluded that the complete feed based on corn forage and king grass on ongole crossbreed cattle composition 50% consentrate + 25% corn forage + 25% king grass increase consumption of NNFE, digestibility of Crude fiber and digetibility of NNFE. Key Words: crude fiber, NNFE, corn forage, ongole crossbreed cattle.